2015
DOI: 10.1590/so100-720320150005420
|View full text |Cite
|
Sign up to set email alerts
|

Spatial distribution of pregnancy in adolescence and associations with socioeconomic and social responsibility indicators: State of Minas Gerais, Southeast of Brazil

Abstract: PURPOSE:To describe associations between pregnancy rates in adolescence and socioeconomic and social responsibility indicators in the municipalities of the State of Minas Gerais, Southeast of Brazil, in the year of 2010. METHODS: Ecological study using data from the Brazilian Live Birth Information System (SINASC). The percentage of live births to adolescent mothers (LBAM) for each municipality was calculated based on the quotient between number of born alive infants of mothers aged 10-19 years old and total n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
5
0
8

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 16 publications
1
5
0
8
Order By: Relevance
“…A respeito da classe socioeconômica e renda, fazer parte da classe C, D ou E (Faler et al, 2013), D ou E (Béria et al, 2020), ter menor renda familiar total (Cesar et al, 2011), fazer parte de família participante do Programa Bolsa Família (Roza & Martinez, 2015), bem como morar em área rural (Fernandes, Santos, & Barbosa, 2019) foram associados com a gravidez na adolescência. Municípios com menor valor de Índice de Desenvolvimento Humano (IDH) (Martinez & Roza, 2020;Roza et al, 2018), com menor Produto Interno Bruto (PIB), com maior incidência de pobreza e com maior percentual de vulneráveis (Martinez et al, 2011) também estiveram associados com a gravidez na adolescência.…”
Section: Veiga Et Al 2019 Maceióunclassified
“…A respeito da classe socioeconômica e renda, fazer parte da classe C, D ou E (Faler et al, 2013), D ou E (Béria et al, 2020), ter menor renda familiar total (Cesar et al, 2011), fazer parte de família participante do Programa Bolsa Família (Roza & Martinez, 2015), bem como morar em área rural (Fernandes, Santos, & Barbosa, 2019) foram associados com a gravidez na adolescência. Municípios com menor valor de Índice de Desenvolvimento Humano (IDH) (Martinez & Roza, 2020;Roza et al, 2018), com menor Produto Interno Bruto (PIB), com maior incidência de pobreza e com maior percentual de vulneráveis (Martinez et al, 2011) também estiveram associados com a gravidez na adolescência.…”
Section: Veiga Et Al 2019 Maceióunclassified
“…This is supported by the suggestion that distance to family planning clinics matters with respect to attenuating risky sexual activities among older adolescents (Bersamin et al, 2011). Therefore, the characteristics of certain places may influence behaviour, values and attitudes, which ensure that populations should be considered within a geographical context (Roza and Martinez, 2015). Despite some risk factors that cannot be controlled or modified, others must be processed to reduce the vulnerability of exposure in this regard (Blake and Bentov, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…12 In Brazil there are few spatial cluster studies of adolescent pregnancy and all of them have demonstrated its relationship with diverse socioeconomic determinants. 3,5,[13][14][15] This study intends to broaden understanding and produce information, not investigated on the individual level, capable of informing decision making regarding addressing this Public Health problem from a collective perspective. To identify socioeconomic and health care determinants of spatial variation in adolescent pregnancy in Brazil in 2014.…”
Section: Introductionmentioning
confidence: 99%